Abundant grain boundaries activate highly efficient lithium ion transportation in high rate Li4Ti5O12 compact microspheres. Issue 3 (20th December 2018) - Ma, Jiaming; Wei, Yinping; Gan, Lin; Wang, Chao; Xia, Heyi; Lv, Wei; Li, Jia; Li, Baohua; Yang, Quan-Hong; Kang, Feiyu; He, Yan-Bing
Abstract : It is a huge challenge for high-tap-density electrodes to achieve high volumetric energy density but without compromising the ionic transportation. Abstract : It is a huge challenge for high-tap-density electrodes to achieve high volumetric energy density but without compromising the ionic transportation. Herein, we prepared compact Li4 Ti5 O12 (LTO) microspheres consisting of densely packed primary nanoparticles. The real space distribution of lithium ions inside the compact LTO was revealed by using scanning transmission electron microscopy with electron energy loss spectroscopy (STEM-EELS) to identify the function of grain boundaries for lithium ion transportation during lithiation. The as-prepared LTO microspheres possess a high tap density (1.23 g cm −3 ) and an ultra-small specific surface area (2.40 m 2 g −1 ). Impressively, the compact LTO microspheres present excellent electrochemical performance. At high rates of 5C, 10C and 20C, the LTO microspheres show a specific capacity of 146.6, 138.2 and 111 mA h g −1, respectively. The capacity retention remains at 97.8% at 5C after 500 cycles. The STEM-EELS results indicate that the lithiation reaction of LTO is firstly initiated at grain boundaries during the high rate lithiation process and then diffuses to the bulk area. The abundant grain boundaries in compact LTO microspheres can form a highly efficient conductive network to preferentially transport the ions, which contributes to high volumetric and gravimetric energy density simultaneously.